The Role of School in the Formation of Morality and Control of Social Deviance in Society: Analysis of Teaching Studies at Al Hasanah Islamic Boarding School Bengkulu - Muhammad Azrul Amirullah; Septiyan Dwi Putra (Lembaga Yasin AlSys, 2025)
This research is driven by the limited strategic role of schools in instilling moral and social values, which contributes to the emergence of deviant behavior among students. Conversely, schools are also responsible for administering educational sanctions and providing counseling to address such behaviors. The study aims to explore and analyze the role of schools in shaping morality and regulating social behavior, with a specific focus on teaching practices at Al Hasanah Islamic Boarding School in Bengkulu. Utilizing a descriptive qualitative approach, the research investigates the school’s contribution to moral development and its influence in maintaining students’ social standing. The findings reveal that moral education at Al Hasanah is implemented through structured religious routines, such as Qur’an recitation, communal prayers, dhikr, and sunnah fasting—along with teacher role modeling, the reinforcement of discipline, and the cultivation of social practices like greeting, smiling, and showing care for others. These practices have effectively fostered student traits such as integrity, discipline, humility, and leadership. Additionally, the Islamic boarding school functions as a social control institution, successfully minimizing deviant behavior and producing individuals capable of becoming positive role models in society. The study affirms that Islamic boarding schools serve not only as centers of religious education but also as agents of social transformation, contributing to the development of a moral, religious, and socially responsible generation.